Probabilistic semi-simple splicing system and its characteristics - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (Universiti Teknologi Malaysia, 2013)
The concept of splicing system was first introduced by Head in 1987. This model has been introduced to investigate the recombinant behavior of DNA molecules. Splicing systems with finite sets of axioms only generate regular languages. Hence, different restrictions have been considered to increase the computational power up to the recursively enumerable languages. Recently, probabilistic splicing systems have been introduced where probabilities are initially associated with the axioms, and the probability of a generated string is computed by multiplying the probabilities of all occurrences of the initial strings in the computation of the string. In this paper, some properties of probabilistic semi-simple splicing systems, which are special types of probabilistic splicing systems, are investigated. We prove that probabilistic semi-simple splicing systems can also increase the generative power of the generated languages.